Amphiphilic Viologen: Electrochemical Generation of Organic Reductant and Pd-Catalyzed Reductive Coupling of Aryl Halides in Water - Kuroboshi, Manabu; Yamamoto, Takashi; Tanaka, Hideo (Synlett, 2013)
Electroreduction of 1,1′-bis(methoxyethoxyethoxyethyl)-4,4′-bipyridinium tosylate generated amphiphilic organic reductants, which promoted the Pd-catalyzed reductive coupling of aryl bromides in water to give the corresponding biaryls. The yields and selectivity of biaryls depended on the length of ethyleneoxy groups and substituents of the aryl bromides.
Keywords: electron transfer; palladium; reduction; coupling; arenes